Silent bloom in a burnt soil: A post ablation pregnancy ending in hysterectomy (East West Medical College Journal, 2026)
Background: Pregnancy following endometrial ablation is rare but associated with severe obstetric complications, including abnormal placentation, uterine rupture, and hemorrhage. Early identification and a multidisciplinary approach are vital in managing these high-risk cases.Case Presentation: We report the case of a 33-year-old woman with a history of endometrial ablation who presented at 8 weeks gestation with severe vaginal bleeding and abdominal pain. Ultrasound confirmed retained products of conception, and surgical evacuation was performed. However, uncontrollable bleeding ensued, prompting a CT scan that revealed active hemorrhage from a uterine artery branch and hemoperitoneum. Laparoscopy was initially planned to investigate suspected uterine perforation, but due to hemodynamic instability and ongoing hemorrhage, an emergency laparotomy and total abdominal hysterectomy were performed. Interventional radiology was consulted but could not proceed due to the emergent nature of the case.Conclusion: This case highlights the high-risk nature of pregnancy after endometrial ablation and the need for urgent, coordinated surgical management in the face of massive hemorrhage. Recognition of complications, prompt imaging, and decisive multidisciplinary action were essential to the patient’s survival.EWMCJ Vol. 14, No. 1, January 2026: 91-93